ҚАРАҚАЛПАҚСТАНДАҒЫ ГЕОГРАФИЯЛЫҚ ОБЪЕКТЛЕРДИҢ БЕЛГИЛЕРИ МЕНЕН АТАЛҒАН АЙЫРЫМ ОРОНИМЛЕР ҲАҚҚЫНДА - Абишов, Г.М. (SCIENCE and SOCIETY, 2021)
The article deals with oronyms formed due to geographical objects in the Republic of Karakalpakstan. The oronyms divided into groups upto the origin and semantic classification. The terms which were formed on the base of geographical object features take important role. In the article these oronyms are shown by dividing into small groups in according to the principles of forming and origin. They are illustrated by the example of oronyms of Karakalpakstan.